Cryostructuring of Polymeric Systems: 68. Evaluation of Poly(vinyl alcohol) Composite Cryogels Filled with Poly(3-hydroxybutyric acid)-Based Microspheres of Different Porous Morphology as Potential Delivery Systems for Drugs of Various Water-Solubility - Dmitrii A. Michurov; Gagik A. Andreasyan; Vladimir I. Lozinsky (Gels)
Poly(3-hydroxybutyric acid)-based microspheres of two types, with and without macropores, were prepared; their morphology and particle size were evaluated. These microspheres were entrapped as disperse fillers into the bulk of macroporous cryogels based on poly(vinyl alcohol) (PVA). It was found that the rigidity of the resultant composite cryogels increased markedly as compared to that of unfilled cryogels of the same PVA concentration. The resulting composites were further tested for their potential to act as drug carriers. With that, simvastatin was included into the filler particles directly in the course of their preparation, followed by entrapment of such drug-loaded microspheres into the PVA cryogel. In turn, ibuprofen sodium salt was introduced into the preliminary prepared cryogels filled with the drug-free microspheres. The experimental study of drug release kinetics showed that due to the non-covalent interactions of both simvastatin and ibuprofen sodium salt with the particles of discrete phase, prolongation of the release processes was observed.